PEMODELAN KONTROLER UNTUK PENGISIAN BATERAI BERSUMBER DARI ENERGI ANGIN DAN SURYA - Annisa Dian Kusuma; Nu Rhahida Arini; Joke Pratilastiarso, (Prosiding Seminar Nasional Terapan Riset Inovatif (SENTRINOV), 2024)
Wind and solar energy are renewable energies that are very abundant in nature and are promising in the future energy sector. In this research, a system is created that allows to control the output power of both renewable energy sources, namely photovoltaic and wind turbines. The control in question is if one of the energy sources gets more power due to differences in climate and weather factors than the other energy source, then the energy source that has a greater output power is utilized. With controllable output power, it is expected to get more optimal results compared to the use of a single energy source or one energy source alone. This research focuses specifically on the battery charging system, therefore a control system is needed that can regulate the output of the energy source that enters the battery. The results obtained before combining the two energy sources are, the electric power from the wind turbine is 19.39Wp and photovoltaic 44.81Wp. Then after the combination produces an electric power of 65.82Wp, this shows that combining energy sources is expected to produce more optimal power compared to using only one source.